Macro-Fiscal Implications of Health Care Reform in Advanced and Emerging Economies : Case Studies. (Policy Papers; Policy Paper ;, 2010)
This supplement provides country case studies on public health care expenditures and reform experiences in eight advanced and six emerging market economies. The case studies for the advanced economies seek to highlight specific episodes of success in containing public health spending during the past 30 years. For the emerging economies, the case studies take a broader approach and examine reform experiences and challenges during the past two decades rather than focusing exclusively on episodes of successful reform. The lessons from the case studies for other countries are integrated into the main Board paper.